OPTIMIZATION OF CONDITIONS FOR THE ACTIVATION OF XANTHINE OXIDASE AND THE FORMATION OF NITRIC OXIDE IN FRESH SHEEP MILK - Mukhamejanova A. S.; Shalakhmetova G. A.; Antipov A. N.; Alikulov Z. (Scientific Journal of Pedagogy and Economics, 2019)
For the detection of sheep milk XO activity a various natural and artificial antioxidants were examined. Among the natural antioxidants L-cysteine was more effective in the stabilization of XO in heated milk. XO of sheep milk activated by heat treatment in the presence of cysteine and molybdenum became able to convert nitrate and nitrite to nitric oxide (NO). Therefore, L-cysteine was used for double purposes: as the protector of enzyme active center against the oxidation during heat treatment of milk and as a reagent for S-nitrosothiol formation. Hypoxanthine, a natural substrate of XO, was the effective electron donor for NaR and NiR activities. Heat treatment of the milk in the presence of exogenous lecithin increased the activity of NaR and NiR of XO and CysNO formation. Thus, during the heat treatment: a) excess of exogenous phospholipids disintegrate the structure of MFGM and b) enzyme molecules denatured partially and their active center became available for exogenous cysteine, molybdenum, hypoxanthine and nitrate or nitrite.